Seasonal Influenza Vaccine Literacy and Hesitancy of Elderly Czechs: An Analysis Using the 5C Model of Psychological Antecedents - Riad, Abanoub; Truksová, Veronika; Koščík, Michal (International journal of public health, 2024)
OBJECTIVES: Seasonal influenza vaccination rates among the elderly in the Czech Republic are alarmingly low, making it one of the least vaccinated countries in Europe. This study explored the role of vaccine literacy and insurance coverage on vaccination status. METHODS: An analytical cross-sectional study was conducted in Summer 2023 using a self-administered questionnaire covering vaccine literacy (functional, interactive, and critical skills), negative perceptions towards influenza vaccination, and the 5C model (confidence, complacency, constraints, calculation, and collective responsibility). Individuals aged 55 and older were included in the study. Mediation analyses assessed the indirect effects of insurance coverage on vaccination status. RESULTS: Significant differences were noted in vaccination rates based on insurance coverage, chronic diseases, regular medication use, and previous COVID-19 and pneumococcal vaccinations. Vaccine literacy, especially interactive and critical skills, was higher among vaccinated individuals. Confidence and collective responsibility were significant promoters, while complacency and constraints were barriers to vaccination. Mediation analyses indicated that negative perceptions, confidence, and collective responsibility significantly mediated the relationship between insurance coverage and vaccination status. CONCLUSION: Enhancing vaccine literacy and addressing psychological antecedents are crucial for improving influenza vaccination rates among the elderly. Policy measures should include improving vaccine literacy, building public confidence, and addressing negative perceptions.
Keywords: Cross-Sectional Studies; Influenza Vaccines; Male; pojistné krytí; zdravotní gramotnost; Health Knowledge, Attitudes, Practice; Česká republika; odkládání očkování; aged; Aged; mužské pohlaví; senioři; průzkumy a dotazníky; Health Literacy; vakcíny proti chřipce; Eastern European People; vakcinace; Czech Republic; senioři nad 80 let; Insurance Coverage; lidé; ženské pohlaví; roční období; zdraví - znalosti, postoje, praxe; Humans; Seasons; health literacy; Vaccination Hesitancy; Vaccination; průřezové studie; Aged, 80 and over; Influenza, Human; influenza; Female; Surveys and Questionnaires; lidé středního věku; vaccination hesitancy; chřipka lidská; Middle Aged; Východoevropané